Fuscoporia ambigua sp. nov., a new species from America and China - Du, Ping; Chen, Qian; Vlasák, Josef (Phytotaxa, 2020)
A new species of Hymenochaetaceae, Fuscoporia ambigua sp. nov., is described based on specimens from the USA and China. The phylogeny, based on the ITS+nLSU+RPB2+TEF1 dataset, revealed that it nested within the Fuscoporia clade, and all the American and Chinese specimens of the new species clustered in a lineage with good support. The new species is characterized by its annual, resupinate basidiocarps with pores measuring 5–6 per mm, aseptate skeletal hyphae, presence of mycelial setae and cystidioles, long hymenial setae (45–75 μm) which are occasionally septate, presence of cystidioles, and ellipsoid basidiospores measuring 4.2–5.2 × 2.8–3.3 μm. Fuscoporia ambigua is very similar and closely related to F. ferruginosa, but the latter species has a perennial growth habit, and short and aseptate hymenial setae (30–44 μm).